Penguatan Harga Pokok Produksi melalui Pendampingan Keuangan: UMKM Keripik Samiler di Desa Wonosunyo - Adhar Putra Setiawan; Tining Haryanti; Rieska Maharani; Marista Oktaviani; Dicky Hikam (Jurnal Kabar Masyarakat, 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in improving the community’s economy. However, many MSME actors still face difficulties in managing business finances. These problems were also experienced by the Samiler Crackers MSME in Betro Hamlet, Wonosunyo Village, Gempol District, Pasuruan Regency, particularly in preparing the Cost of Goods Manufactured (COGM), determining selling prices, and managing simple financial reports. This community service activity aimed to improve the understanding and skills of MSME actors in financial management. The implementation method used a Participatory Action Research (PAR) approach through observation, socialization, training, mentoring, and evaluation stages. The results of the activity showed that MSME actors were able to prepare a more detailed Cost of Goods Manufactured by classifying production costs, understand selling price determination based on raw material costs and product quality, and conduct simple financial recording of cash inflows and cash outflows. In addition, simple financial reports helped MSME actors identify income levels and business conditions. This mentoring activity had a positive impact on improving MSME financial management capabilities and is expected to support the sustainability and development of the Samiler Crackers business in Wonosunyo Village.Micro, Small, and Medium Enterprises (MSMEs) play an important role in improving the community’s economy. However, many MSME actors still face difficulties in managing business finances. These problems were also experienced by the Samiler Crackers MSME in Betro Hamlet, Wonosunyo Village, Gempol District, Pasuruan Regency, particularly in preparing the Cost of Goods Manufactured (COGM), determining selling prices, and managing simple financial reports. This community service activity aimed to improve the understanding and skills of MSME actors in financial management. The implementation method used a Participatory Action Research (PAR) approach through observation, socialization, training, mentoring, and evaluation stages. The results of the activity showed that MSME actors were able to prepare a more detailed Cost of Goods Manufactured by classifying production costs, understand selling price determination based on raw material costs and product quality, and conduct simple financial recording of cash inflows and cash outflows. In addition, simple financial reports helped MSME actors identify income levels and business conditions. This mentoring activity had a positive impact on improving MSME financial management capabilities and is expected to support the sustainability and development of the Samiler Crackers business in Wonosunyo Village